Mathematical modelling and research of passenger flows in marine passenger port - Vladimir A. Fetisov; Nikolay N. Maiorov (Naše More (Dubrovnik), 2017)
Modern passenger terminals are characterized by dynamic processes variability, diverse options consideration, taking into account the criteria of safety, reliability analysis and the continuous research of passenger processing. For any modern marine passenger terminal it is necessary to use the tool to simulate passenger flows. In this way it is possible to obtain the analytical information and use it for decision-making when solving the problem of the amount of personnel required for passenger services.in line with the original ship arrival schedule, to solve problems of forecasting groups at the terminal. Of particular relevance is the choice of the mathematical transport model and the practical conditions for the implementation of the model in the real terminal operation. In this article the analysis technique of simulation-based terminal services, provides a mathematical model of passenger movement inside the terminal. Also, the conditions of implementation of the transportation model during the operation of marine passenger terminal are examined. The object of the research is the marine Passenger Port of St. Petersburg "Marine Facade". The paper discusses advantages of using such systems and their introduction in the early stages of operation of the terminal. In addition, the conclusion about the effectiveness of such systems for the analysis of the correctness of internal space of the marine terminal. The study represents an example of analytical information used for the forecast of the terminal operations, the analysis of the workload and efficiency of the organization of the marine terminal.